REVIEW OF CRIMINAL POLICY ON COUNTERING ECONOMIC CRIMES - Abdurrahman Harits Ketaren (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of this study is to find out the development of economic crimes. Legal materials obtained in the study of literature, laws and regulations, and articles, are described and linked in such a way that it can be presented in a more systematic writing to answer the research problems that have been formulated. There is an international tendency today to pursue policies that prioritize or put forward criminal law in tackling certain crimes as a means of deterrent. Thus, the position of criminal law in anticipating violations related to administrative law can be used as 'ultimum remedium' and in certain cases certain acts can also be applied as 'primum remedium'. justification for criminalization for an offender, but still should not eliminate his human power in achieving new values and new adaptations. Therefore at the same time, the offender must be directed through various 'improvement efforts' to achieve a fuller form as a human being.